MRI in acute ligamentous injuries of the ankle - Martella, Ilenia; Azzali, Emanuele; Milanese, Gianluca; Praticò, Francesco Emanuele; Ruggirello, Margherita; Trunfio, Vincenzo; Parziale, Raffaele; Corrado, Michele; Della Casa, Giovanni; Capasso, Raffaella; De Filippo, Massimo (Acta Biomedica Atenei Parmensis, 2016)
Ankle sprains are the most common lower limb injuries and affect more frequently young athletes; imaging is needed for an accurate diagnosis of such traumatic injuries. The purpose of this review is to analyse the magnetic resonance (MR) findings of both normal and pathological ankle’s ligaments; indeed, MRI is the gold standard for the diagnosis of acute traumatic injuries and is useful for differentiation of the causes of ankle instability as well as for pre-operative planning